2023
DOI: 10.1186/s12889-023-15749-x
|View full text |Cite|
|
Sign up to set email alerts
|

Global prevalence, incidence, and outcomes of alcohol related liver diseases: a systematic review and meta-analysis

Abstract: Background Alcohol related liver disease (ARLD) is one of the major chronic liver diseases worldwide. This review aimed to describe the global prevalence, incidence, and outcomes of ARLD. Methods Medline, Embase, The Cochrane Library, and China National Knowledge Infrastructure (CNKI) were searched from inception to May 31, 2022. The language was restricted to English or Chinese. According to the criteria, articles describing the basic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 269 publications
(299 reference statements)
0
12
0
Order By: Relevance
“…[4][5][6]15 The prevalence of ALD is estimated at around 5% of the global population, although estimates vary considerably. 16 If an individual who drinks fewer than 14 drinks per week is used as a reference, the hazard ratio (HR) for incident cirrhosis associated with drinking 14-28 drinks per week is about 2.3 for men and 3.5 for women, and the HR associated with drinking 28-42 drinks per week is 7.0 and 16.2 for men and women, respectively. 17 Long-term followup of 3453 patients with biopsy-proven ALD showed that 5-year cumulative mortality was 40.9% in patients with ALD compared with 5.8% in the matched reference population with a near five-fold increase in death.…”
Section: Epidemiology Of Alcohol-related Liver Diseasementioning
confidence: 99%
“…[4][5][6]15 The prevalence of ALD is estimated at around 5% of the global population, although estimates vary considerably. 16 If an individual who drinks fewer than 14 drinks per week is used as a reference, the hazard ratio (HR) for incident cirrhosis associated with drinking 14-28 drinks per week is about 2.3 for men and 3.5 for women, and the HR associated with drinking 28-42 drinks per week is 7.0 and 16.2 for men and women, respectively. 17 Long-term followup of 3453 patients with biopsy-proven ALD showed that 5-year cumulative mortality was 40.9% in patients with ALD compared with 5.8% in the matched reference population with a near five-fold increase in death.…”
Section: Epidemiology Of Alcohol-related Liver Diseasementioning
confidence: 99%
“…Phosphatidylethanol (PEth) is an accurate and specific biomarker that detects recent alcohol use. [1] PEth testing can be performed on whole blood or dried blood spots, has a wide detection window of alcohol use within 2-4 weeks, and can provide an estimate on the level of alcohol consumption. [2] As such, PEth has advantages over other markers of alcohol consumption such as breathalyzer or blood alcohol levels (window of detection is too brief), carboxy-deficient transferrin (inaccurate), or nonspecific markers such as serum gamma-glutamyl transpeptidases (insensitive and inaccurate).…”
Section: Making the Best Use Of Testing For Blood Phosphatidylethanolmentioning
confidence: 99%
“…It also represents a new diagnostic scheme that subclassifies SLD by etiology, 4 with the 2 most common being metabolic dysfunction–associated steatotic liver disease (MASLD, formerly known as NAFLD) and alcohol-associated liver disease (ALD). These affect approximately 30% and 5% of the general population, respectively 5,6 …”
Section: Introductionmentioning
confidence: 99%